Faktor - Faktor Yang Mendorong Adopsi Qris sebagai Solusi Pembayaran Digital untuk Mempermudah Transaksi UMKM - Sriyono, Sriyono; Adam, Julian; Dwi Kinasih, Ramona; Agustina, Dayuk; Maulidah, Ummul; Al Adawiyah, Eka Robi’atul (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
Elaborating on the factors that encourage QRIS adoption by MSMEs is the aim of this study. Literature review is the research method that we use. Data was obtained through analysis of related articles that reveal the views of industry players. The study results prove that there are factors that encourage the adoption of QRIS by MSMEs, namely: (1) QRIS is easy to use and does not require special equipment. (2) The security of QRIS is guaranteed by Bank Indonesia. (3) QRIS can speed up the transaction process and increase the operational efficiency of MSMEs. (4) Using QRIS can increase MSME sales because it attracts more customers who use digital payments. It is hoped that with more and more MSMEs adopting QRIS, financial transactions will become more efficient, easier and safer, so that they can encourage the economic growth of MSMEs in Indonesia. However, there are still several inhibiting factors that need to be improved by the government and Bank Indonesia.